Review: Metode-Metode Ekstraksi - Rismiyati; Adinda Strianti Oktari; Annisa Nurrahman; Baiq Mekia Rahmayanti; Novita Aulia; Anggit Sunarwidhi (Sci-tech Journal, 2025)
Extraction is a crucial process in obtaining bioactive compounds from various materials. This literature review aims to discuss different extraction methods along with their advantages and limitations in various applications. Extraction methods can be categorized into conventional and modern techniques. With technological advancements, extraction methods have become more diverse and efficient. Selecting the appropriate method is essential for extraction success, depending on the type of material and the compounds to be obtained. One of the most efficient modern methods is Microwave-Assisted Extraction (MAE), which offers advantages such as higher yield, shorter extraction time, and reduced solvent usage compared to conventional methods.